2009
DOI: 10.1177/0748233709103413
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant effects of vitamin A, C, and E on aflatoxin B1-induced oxidative stress in human lymphocytes

Abstract: The aim of this study was to investigate the possible protective role of vitamin A, C, and E on aflatoxin B(1)-induced in human lymphocytes using biochemical approaches. The control group received dimethyl sulfoxide, the second group of cultures were administered aflatoxin B(1) (AFB(1)) at a dose of 5 muM. The other group of cultures were treated with AFB(1)+vitamin A (0.5 and 1.0 and 1.5 microM) and AFB(1)+vitamin C (25, 50, and 100 microM) and AFB(1)+vitamin E (40, 100, and 200 microM). The results of this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 40 publications
3
67
2
Order By: Relevance
“…The effects of vitamin E seemed to be stronger in obese patients compared with controls. Our findings corroborated previous studies [56] [60]- [62].…”
Section: Discussionsupporting
confidence: 93%
“…The effects of vitamin E seemed to be stronger in obese patients compared with controls. Our findings corroborated previous studies [56] [60]- [62].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, MDA was significantly elevated in the wheat milling workers with high serum levels of AFB1/alb compared to the controls. The increased production of MDA; as a late biomarker of oxidative stress regardless of the way it is induced, could explain the dose-dependent high cytotoxic and genotoxic potential of AFB1 [30]. It was reported that AFB1 generates ROS that has an important contribution in the hepatic damaging process [7], and that could explain the significant correlation between MDA and the liver enzymes AST, GGT and P53 detected in the present study.…”
Section: Discussionsupporting
confidence: 52%
“…Exposure to heavy metal (Ni, Co, Cr, Zn) levels in the growth medium resulted in increased vitamin A of bean plants (Fig 1A, 2A, 3A, 4A). Vitamin A (retinol) is the most eff ective naturally occurring quencher of singlet oxygen; it is a radical scavenger and an effective chain-breaking antioxidant (Alpsoy et al, 2009). Vitamin E is a potent lipid-soluble antioxidant, with the ability to quench free radicals directly, and functions as a membrane stabilizer (Clarke et al, 2008).…”
Section: Discussionmentioning
confidence: 99%